Pemanfaatan Analisis Bibliometrik Menggunakan VOSViewer untuk Pemetaan Tren Publikasi TPACK dan Critical Thinking Skills - Andi Alim Syahri; Irwan Akib; Sukmawati, Sukmawati (Prosiding SISFOTEK, 2024)
This study aims to analyze the development of studies related to "TPACK" and "Critical Thinking Skills" based on bibliometric analysis of a number of journal articles published in the Google Scholar database. This research identifies scientific gaps as a reference for further research. TPACK and Critical Thinking Skills have an important role in realizing 21st century learning in education. This research method uses a bibliometric analysis approach by collecting article data from 2019 to 2023. Data collection was supported by VOSviewer software using the keywords "TPACK" and "Critical Thinking Skills", and a total of 500 articles were analyzed. The results showed an increasing trend of research on TPACK and Critical Thinking Skills, and several topics/keywords were found that can be used as a basis for further research. The bibliometric analysis provides valuable information and knowledge about the development of "TPACK" and "Critical Thinking Skills" research, and the results of this study can serve as a basis for possible new research in the future. The findings can provide important information for educational researchers and practitioners in understanding current research trends and also help set the direction for more in-depth research in the future.